Implementation of IMWR (Inspiring-Modeling-Writing-Reporting) scaffolding on students cognitive learning outcome in the stoichiometry topic - Langitasari, Indah; Sari Siti Aisyah, Ratna; Elis Sya'adah, Siti (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2023)
Stoichiometry is one of the essential chemistry topics that is an abstract concept, involves complex calculations, and is related to other chemical concepts. It can cause not a few students to have difficulty learning it. Scaffolding is needed in the learning process of stoichiometry concepts to help students understand concepts more easily and improve learning outcomes. This research aims to determine differences in students' cognitive learning outcomes on the stoichiometry topic after implementing the IMWR scaffolding model. This research used experimental research with the one-group pretest-postest design. Respondents were 32 high school students who were determined by purposive sampling. The instrument test consisted of 32 items of essays that were valid and reliable. Data is collected and carried out through pretest and posttest. The differences in students' cognitive learning outcomes were analyzed descriptively using the N-gain test and statistical analysis using the paired sample t-test. The paired sample t-test showed a significance value of 0.000 (sig. <0.05), meaning there were differences in student learning outcomes after implementing the IMWR Scaffolding learning model. However, the resulting difference is not significant and is in a low category (N-gain 0.27). Implementing IMWR scaffolding needs to be designed as best as possible by paying attention to students' character to help students understand the concept using procedural knowledge, which impacts better learning outcomes.